Improvement of Seismic Capacity of Reinforced Concrete Frame Building by Installing Infilled Walls - yeon Seo, Soo; cheol Lee, Guncheol; joe Yoon, Seung (International Journal of Engineering and Technology, 2018)
This paper aims to analytically examine the retrofit effect of two different construction methods for the infilled walls by RC and form block. Accordingly, it compares the performance point on the demand-capacity curve via the capacity spectrum method, and the degree of plastic deformation of the structure between RC and form block infilled walls.As for the gravity load on the building that extended from the three-story to the five-story structure, the external force on the beam located at the center of the second floor was 2.4 times higher than the internal strength, and for the lateral force, the external force on the beam on the floor of the second core part increased by up to 2.6 times to the internal strength, showing that the reinforcement on the members would be necessary. The members of the building extended to the five stories were determined to be susceptible to gravity load and lateral load, and the load combination of each member showed that it would be effective to install the infilled wall on the shorter side for gravity load and on the longer side for lateral load.Â Â